A Self‐Delivery Nanodrug Simultaneously Inhibits COX‐2/PGE2 Mediated Inflammation and Downregulates PD‐L1 to Boost Photoimmunotherapy - Lai, Jin‐Mei; Chen, Pei‐Ling; Shi, Qun‐Ying; Xie, Yong‐Qi; Jiaerheng, GuliJiayina; Liu, Li‐Han (Advanced healthcare materials, 2024)
Phototherapy promotes anti‐tumor immunity by inducing immunogenic cell death (ICD), However, the accompanying inflammatory responses also trigger immunosuppression, attenuating the efficacy of photo‐immunotherapy. Herein, they co‐assembled a cell‐membrane targeting chimeric peptide C16‐Cypate‐RRKK‐PEG8‐COOH (CCP) and anti‐inflammatory diclofenac (DA) to develop a nanodrug (CCP@DA) that both enhances the immune effect of phototherapy and weakens the inflammation‐mediated immunosuppression. CCP@DA achieves cell membrane‐targeting photodynamic and photothermal synergistic therapies to damage programmed death ligand 1 (PD‐L1) and induce a strong ICD to activate anti‐tumor response. Simultaneously, the released DA inhibits the cycoperoxidase‐2 (COX‐2)/prostaglandin E2 (PGE2) pathway in tumor cells to inhibit pro‐tumor inflammation and further down‐regulate PD‐L1 expression to relieve the immunosuppressive microenvironment. CCP@DA significantly inhibited tumor growth and inflammation both in vitro and in vivo, while maintaining a potent anti‐tumor immune response. Additionally, it exhibits excellent anti‐metastatic capabilities and prolongs mouse survival time with a single dose and low levels of near‐infrared (NIR) light exposure. This work provides a valuable strategy to control the therapy‐induced inflammation for high‐efficiency photoimmunotherapy. Phototherapy promotes anti‐tumor immunity by inducing immunogenic cell death, but the accompanying detrimental inflammatory responses also trigger immunosuppression, attenuating the efficacy of photoimmunotherapy. Herein, a nanodrug (CCP@DA) that coassembled from cell‐membrane targeting chimeric peptide (CCP) and anti‐inflammatory diclofenac (DA) to both enhance the immune effect of phototherapy and weaken the inflammation mediated immunosuppression is developed.